Atando los nodos sueltos: blockchain para la reducción de corrupción en las licitaciones públicas de Proinversión - Masumura Ynami, Dana Lorena (2021)
The public-private partnerships in Peru have been created with the intention of establishing a middle ground between privatizations and the absolute control of the State in matters of public interest. The most characteristic example of this are concessions. Despite the benefits that this entails, high levels of corruption are revealed within the concession procedures, which reduces the credibility of the public private associations. Faced with this problem, the alternative of e-procurement arises, which implies the use of technologies to ensure the transparency and efficiency of public tenders. Within this, the blockchain functions as an instrument applicable to concession procedures.In this article, the authors analyze how corruption appears as a latent problem in concessions, and then go on to answer why blockchain is an alternative to fight against it. Subsequently, theystudy how it would be possible to apply this in the concession procedures in charge of ProInversión. Finally, they identify the challenges that it would entail and analyze whether the use of the proposed tool is effective.